Pruritus in cholestasis: facts and fiction - Beuers, Ulrich; Kremer, Andreas; Bolier, Ruth; Elferink, Ronald P. J. Oude (Hepatology, 2014)
Pruritus is a common symptom in patients with cholestatic liver diseases such as primary biliary cirrhosis, primary sclerosing cholangitis, intrahepatic cholestasis of pregnancy, or hereditary pediatric cholestatic disorders and may accompany, although less frequently, many other liver diseases. Recent findings indicate that lysophosphatidic acid (LPA), a potent neuronal activator, and autotaxin (ATX; ectonucleotide pyrophosphatase/phosphodiesterase 2), the enzyme which forms LPA, may form a key element of the long-sought pruritogenic signaling cascade in cholestatic patients suffering from itch. Serum ATX, but no other pruritogen candidate studied so far, correlates with pruritus intensity and responds to therapeutic interventions. In this comprehensive review, we provide a short update on actual insights in signal transmission related to pruritus and discuss pruritogen candidates in cholestasis. We also summarize evidence-based and guideline-approved as well as experimental therapeutic approaches for patients suffering from pruritus in cholestasis.
EVALuna2:1864